Steady state in a cross-diffusion predator–prey model with the Beddington–DeAngelis functional response. (February 2019) - Meng, Qiong; Yang, Lili
Abstract: The purpose of this paper is to study the existence of steady state in a linear cross-diffusion predator–prey model with Beddington–DeAngelis functional response. The proofs mainly rely on Fixed point index theory and analytical techniques.